How to Differentiate Segmental Colitis Associated With Diverticulosis and Inflammatory Bowel Diseases. (October 2016) - Cassieri, Claudio; Brandimarte, Giovanni; Elisei, Walter; Lecca, Giuseppina P.; Goni, Elisabetta; Penna, Antonio; Picchio, Marcello; Tursi, Antonio
Abstract : The segmental colitis associated with diverticulosis, " better known by its acronym "SCAD, " is a chronic inflammatory process localized in the colonic area presenting diverticulosis, and therefore mainly in the sigmoid colon. By definition, both the rectum and the right colon are spared from any inflammation both endoscopically and from a histologic point of view. Recent data have hypothesized that SCAD may be an independent clinical entity within the inflammatory bowel disease set of diseases. Compared with inflammatory bowel disease, SCAD seems to have a more benign outcome, with low rate of complications.